The effect of gender on spine pain in office workers - Analay Akbaba, Yıldız; Yeldan, İpek and Kuru, Tuğba and Zengin, Ayşe and Kostanoğlu, Alis and Tekeoğlu, Anıl and Tarakçı, Devrim (Cerrahpaşa Medical Journal, 2019)
Objectives: This study was designed for determining that cervical, back and lumbar pain existence, degree of the pain and whether this pain interrupts their working performance at the last 1 week period and there is a difference between male and female population. Methods: The pain questionnairy form which is contain cervical, back and lumbar regions has been applied to the subjects by physiotherapist. Precence of pain, tingle, discomfort at cervical, back and lombar regions, pain intensity (mild-moderate-severe), the level of pain that interferes working exemined by the questionnaire. Results: Most painful region was neck (85.6%) for women and lumbar region (47.5%) for men. Women had felt the pain so much severe in the back(15.5%) and men had felt in the lumbar region (7.5%). When the pain interferes with business women felt the pain in neck region (36.1%) and men felt in lumbar region (28.7%). Women felt pain more frequently than man (p=0.001). Conclusion: As a result, pain was more frequent in the lumbar region for men and neck region for women. Most painful region was lumbar in men and back in women. The pain that interferens with business for men was at lumbar region and neck region for women. For women pain feeling and the degree of pain at entire vertebral colon is statistically higher so that may be explained by high pain perception in women. The pain that interfere with working for women is more frequent in neck and back region.